How shift work influences anxiety, depression, stress and insomnia conditions in Italian nurses: an exploratory study: Shift work in Italian nurses - Vitale, Elsa; Lupo, Roberto; Artioli, Giovanna; Mea, Rocco; Lezzi, Pierluigi; Conte, Luana; De Nunzio, Giorgio (Acta Biomedica Atenei Parmensis, 2023)
Background and aim of the work. Evidence suggested that the nursing profession could be considered as a very complex profession also for nurses themselves. To investigate how shift work influence nurses’ health also considering anxiety, depression, stress and insomnia conditions. Methods. An on-line cohort observational study was conducted during May 2022 to 408 nurses. Results. 408 nurses were on-line recruited. Most of the nurses recruited worked also during the night shift (73.3%) and were very young (p